English Tense and Aspect: EFL Problems That Chhulung Learners Have - Rai, Ichchha Purna (Journal of NELTA, 2013)
The paper deals with English and Chhulung* tense and aspect systems. Tense and aspect are important components in grammar of any language. This paper focuses on the differences between English and Chhulung tense and aspect systems and analyzes the EFL problems of Chhulung learners of English in learning English tense and aspect. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 61-69 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8093